Harmful gun behaviour and perceived collective efficacy: evidence from a cross-national study of youth detainees. Issue 2 (3rd April 2022) - Cook, Steven; Bruno, Tara; Erickson, Patricia G.; Butters, Jennifer E.; Harrison, Lana
ABSTRACT: This paper examines the patterns of harmful weapon behavior and the protective influence of perceived collective efficacy on harmful weapon behavior among a cross-national sample of youth detainees in Toronto and Philadelphia. Despite different firearms policies, detained youth in both cities reveal considerable knowledge of where to get a gun. Multivariate analyses reveal that participating in gang fights, non-violent delinquency, and neighborhood gun markets are significantly related to harmful gun behavior in both cities. Only one collective efficacy subscale, perceived social cohesion, exerted a protective influence on harmful gun behavior among youth in both cities. These results suggest that in the absence of "strong ties, " reflected in family and residential stability, there may be added value in the "weak ties" provided by the community, making social cohesion an important protective characteristic for this high-risk group of youthful detainees. The significance of the findings, limitations, and potential policy implications are discussed.